Sound Roots: Pernambuco culture as a starting point for music education - Santa Cruz, Jevison (Revista do Colóquio, 2025)
This paper aims to present how a fourth-grade class from a school in the municipality of Abreu e Lima, Pernambuco, began their musical studies through the Art subject, in a project entitled "With Alceu and Gonzaga at School: Musical Experiences Based on Pernambuco Culture." The methodology adopted was based on a qualitative approach, in the category of experience report. The dynamics of the classes were guided by principles of the musical pedagogies of Zoltán Kodály and Carl Orff. As a result, it was observed that the students systematically learned about two great artists of Pernambuco music, improved aspects related to communication, autonomy, empathy, respect for the time of others, and organization, in addition to being encouraged to understand music as a space for identity construction.
Keywords: music education, pernambuco culture, identity construction.